Selenoprotein Transcript Level and Enzyme Activity as Biomarkers for Selenium Status and Selenium Requirements of Chickens (Gallus gallus) - Li, Jin-Long (PLoS One, 2016)
The NRC selenium (Se) requirement for broiler chicks is 0.15 μg Se/g diet, based primarily on weight gain and feed intake studies reported in 1986. To determine Se requirements in today’s rapidly growing broiler chick, day-old male chicks were fed Se-deficient basal diets supplemented with graded levels of Se (0, 0.025, 0.05, 0.075, 0.1, 0.2, 0.3, 0.5, 0.75, and 1.0 μg Se/g) as Na(2)SeO(3) (5/treatment). Diets contained 15X the vitamin E requirement, and there were no gross signs of Se-deficiency. At 29 d, Se-deficient chicks weighed 62% of Se-supplemented chicks; 0.025 μg Se/g reversed this effect, indicating a minimum Se requirement of 0.025 μg Se/g diet for growth for male broiler chicks. Enzyme activities in Se-deficient chicks for plasma GPX3, liver and gizzard GPX1, and liver and gizzard GPX4 decreased dramatically to 3, 2, 5, 10 and 5%, respectively, of Se-adequate levels, with minimum Se requirements of 0.10–0.13 μg Se/g, and with defined plateaus above these levels. Pancreas GPX1 and GPX4 activities, however, lacked defined plateaus, with breakpoints at 0.3 μg Se/g. qPCR measurement of all 24 chicken selenoprotein transcripts, plus SEPHS1, found that SEPP1 in liver, GPX3 in gizzard, and SEPP1, GPX3 and SELK in pancreas were expressed at levels comparable to housekeeping transcripts. Only 33%, 25% and 50% of selenoprotein transcripts were down-regulated significantly by Se deficiency in liver, gizzard and pancreas, respectively. No transcripts could be used as biomarkers for supernutritional Se status. For export selenoproteins SEPP1 and GPX3, tissue distribution, high expression and Se-regulation clearly indicate unique Se metabolism, which may underlie tissues targeted by Se deficiency. Based on enzyme activities in liver, gizzard, and plasma, the minimum Se requirement in today’s broiler chick is 0.15 μg Se/g diet; pancreas data indicate that the Se requirement should be raised to 0.2 μg Se/g diet to provide a margin of safety.